Investigation of mechanical and fracture properties of wire and arc additively manufactured low carbon steel components. (October 2020) - Ermakova, Anna; Mehmanparast, Ali; Ganguly, Supriyo; Razavi, Javad; Berto, Filippo
Highlights: Mechanical and fracture properties of WAAM components are characterised. The hardness and yield strength of ER100S-1 walls are higher than ER70S-6. The yield and ultimate tensile strength are slightly higher in horizontal samples. The fracture toughness for ER70S-6 is 88% higher than ER100S-1. ER100S-1 fracture toughness results are location dependent. Abstract: Wire and Arc Additive Manufacturing (WAAM) technology offers efficient fabrication of large scale products and is currently being implemented across various industries. In this study, an experimental investigation has been carried out to characterise the mechanical and fracture properties of WAAM components made of ER70S-6 and ER100S-1 metal wires. Microhardness, tensile and fracture toughness tests have been performed on the specimens extracted from the WAAM built walls which were fabricated using an oscillating pattern. The specimens were extracted from different locations, at the top and bottom of the WAAM walls, in two different orientations with respect to the deposition direction. The results show that the material hardness and yield strength of ER100S-1 built wall are higher than ER70S-6 by 62% and 42%, respectively. Moreover, in the walls made with both materials, the yield and ultimate tensile strength values were found to be slightly higher in specimens extracted in deposition (horizontal) direction when compared to specimens extracted in the built (vertical) direction. The average value of fracture toughness parameter for ER70S-6 has been found to be 88% higher than ER100S-1 material. Furthermore, the results show that the specimen extraction location in ER100S-1 wall significantly influences the fracture toughness values obtained from experiments. The results from this study have been compared with those available in the literature and discussed in terms of the mechanical and fracture properties effects on structural integrity assessment of WAAM components.